Assessment of Mangrove Sediment Quality Parameters from Different Seasons, Zones and Sediment Depths - Ahmad Mustapha Muhammad Pazi; Waseem Razzaq Khan; Noraini Rosli; Ainuddin Ahmad Nuruddin; Seca Gandaseca (Jurnal Manajemen Hutan Tropika, 2022)
Heavy metal concentrations have risen throughout Malaysia's coastline because of industrial wastewater discharge, affecting mangrove ecology significantly. Lead (Pb), Zinc (Zn), Chromium (Cr), and Nickel (Ni) were used to establish the Mangrove Sediment Quality Index (MSQi), which assesses and monitors the quality of mangrove sediment. This study was conducted at Matang Mangrove Forest Reserve (MFFR) in Perak, Malaysia to examine changes in MSQi features across seasons, mangrove zones, and sediment depths at three separate MMFR locations. Sediment samples were taken using auger in two different seasons (dry and wet seasons). After the silt was removed using aqua regia techniques, heavy metals were examined using an Atomic Absorption Spectrophotometer. According to MSQi criteria in various seasons at three different locations, the highest concentration of heavy metals (HMs) was detected in the dry season in the least disturbed region at three different locations. During dry seasons, only Cr and Ni levels are higher in moderately and highly disturbed areas. Pb and Zn levels in moderately and highly disturbed areas are higher than in least disturbed areas during the rainy season. MSQi parameters in different mangrove zones at three locations showed that most HMs content is highest in the landward zone and it can be concluded that HMs sources are anthropogenic. Furthermore, MSQi measurements at three locations revealed that heavy metals content is highest at 015 cm and lowest at other depths.